Difference in Initial Treatment, Temperature, and Drying Time on the Organoleptic Properties of Gembus Tempe Flour: Perbedaan Perlakuan Awal, Suhu, dan Waktu Pengeringan Terhadap Sifat Organoleptik Tepung Tempe Gembus - Putri, Rianti Nadila Susana; Astuti, Nugrahani; Widagdo, Andika Kuncoro; Purwidiani, Niken; Lebdoyono, Rendra (jurnal makanan tropis dan teknologi agroindustri, 2025)
This study aims to determine the effect of pretreatment, temperature, and drying time on the organoleptic properties of tempeh gembus flour. Tempe gembus is a fermented product derived from tofu waste with high protein content, but it has limitations in terms of shelf life and sensory characteristics that are difficult to accept in society. This study employed an experimental design with variations in pre-treatment (steaming and roasting), drying temperature (70°C and 80°C), and drying time (5 and 6 hours). Trained panelists conducted sensory evaluations to assess the color, aroma, taste, texture, and appearance of the resulting flour. Based on the sensory evaluation, the best tempe gembus flour was produced with a pre-treatment of 15 minutes of steaming, dried at 80°C for 5 hours. Chemical analysis of the best sample revealed a composition of 42.15% carbohydrates, 33.56% protein, 5% fat, 11.95% moisture, 0.31% ash, and 6.87% fiber.